Mystical theologian: the work of Vladimir Lossky - Nichols, Aidan (Gracewing, 2017)
Vladimir Nikolaevich Lossky, born in 1903, was not only seminal in the development of Orthodox theology in its Diaspora after the Russian Revolution, and a major figure in twentieth-century European theological history, but also one of those whose work can inspire a serious Christian life. This book is not so much preoccupied by 'placing' Lossky within the world of patristic scholarship or the history of Russian religious thought, but rather, on Lossky's substantive spiritual teaching - and, accordingly, that of the teachers, especially ancient and mediaeval, he commended. Its principal intention is of communicating this teaching. The title echoes Lossky's own in his best known book, The Mystical Theology of the Eastern Church, a work choc-a-bloc with doctrinal reflection. However it concentrates perhaps more on his final, posthumously published, lecture course, Théologie dogmatique. Born in Wilhelmine Germany, brought up in Tsarist Russia, educated at universities in St Petersburg, Prague and Paris, deeply influenced by early study of the writings of the mediaeval Latin West, and living and working in France, Vladimir Lossky was ideally placed to provide a link between Orthodoxy and the Christian West. To go deep into Lossky, cordial concern for the spiritual and intellectual concern for the propositional must walk hand in hand. The consequent initiation into the depths of divine revelation Lossky can supply will be likely to profit in both heart and mind anyone who hears his message and seeks in coherent fashion to put it into effect